Ecological education of students of general schools: modern approaches - MARGLAMOVA, Kamilla (Continuing Professional Education: Theory and Practice, 2019)
The paper deals with the analysis of the modern psychological and pedagogical approaches to the problem of ecological education. The core, goal and features of this process are determined. The attention is paid to the formation of the gumanistic values and students’ valuable attitude to the nature